Qualitative dataset on UPLC-QTOF/MS tentative identification of phytochemicals from bioactive extract of Ipomoea mauritiana Jacq. - Alam, Istiak; Forid, Md. Shaekh; Roney, Miah; Mohd Fadhlizil Fasihi, Mohd Aluwi; Huq, AKM Moyeenul (Elsevier Inc., 2021)
The current data report describes the predictive identification of phytochemical constituents in the bioactive extract of Ipomoea mauritiana (IM) whole plant. For several formulations this plant was commonly used as ‘Vidari’ for Ayurvedic medicine. Traditionally, IM tubers are used to alleviate spinal cord pain, improve breast milk, as a tonic, increase sperm count and treating jaundice. The methanol extract can potentially scavenge free radicals and possess antibacterial activity that could be correlated with its chemical composition. So it is crucial to identify the major compounds of IM. An ultra-performance liquid chromatography coupled electrospray ionization quadrupole time-of-flight mass spectrometry (UPLC-ESI-QTOF/MS) method was adopted to detect the flavonoids, saponins, alkaloids, terpenoids in IM methanol extract. Data presented here is related to a published work Antioxidant and antibacterial activity of Ipomoea mauritiana Jacq.: A traditionally used medicinal plant in Bangladesh (Alam et al., 2020). Secondary metabolites were analyzed by the comparison of the mass fragmentation arrangements with Waters UNIFI library that enables for positive identification of the compounds based on the spectral match.